PERKEMBANGAN DAN TANTANGAN PASAR MODAL INDONESIA - FAIZA MUKLIS (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2016)
The capital market is one indicator of a country's economic progress. The existence of the Indonesian capital market began the establishment has undergone several ups and downs that can be seen from the JCI indicators fluctuated. It is as a result of globalization and economic integration that lead to the performance of the capital markets is highly dependent on the performance of the national economy, regional, and international. The greater role of local investors are needed to encourage the Indonesian capital market to make it more resistant to a variety of crises and shocks. The population of the Indonesian middle class that has grown relatively large, an opportunity that can be exploited to encourage them to engage inactive invest in capital markets. Meanwhile, some of the challenges in the development of capital markets must also be addressed among others, the limited types of securities traded, the rules for the protection of the rights of investors, the